Insights into antimicrobial resistance genotype and potential virulent traits of an extensively drug-resistant Acinetobacter baumannii sequence type ST2 - Nguyen, Quang Huy; Hoang, Khanh Linh; Do, Bich Ngoc; Nguyen, Thai Son; Tran, Thi Thanh Tam (Vietnam Journal of Biotechnology, 2025)
Carbapenem-resistant Acinetobacter baumannii has been ranked as the priority 1 pathogen and is urgently needed for the development of new antimicrobials. Understanding the genetic determinants associated with antibiotic resistance and virulence can help to control the resistant evolution, decide on treatment and have appropriate prevention methods. The present study aimed to characterize the genomic features of an extensively drug-resistant (XDR) A. baumannii sequence type ST2. Phenotypic-drug susceptibility testing was conducted against 28 antibiotics. Whole genome sequencing was performed, followed by an analysis of Clusters of Orthologous Genes (COG), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, multilocus sequence typing (MLST), genetic determinants associated with resistance and virulence, and mobile genetic elements. A. baumannii VD610 was resistant to 26 antibiotics and identified as an extensively antibiotic-resistant phenotype. The genome size of A. baumannii VD610 was 3,765,945 bp, comprising a circular chromosome and two plasmids. The COG annotation identified 3012 genes that could be classified into 22 functional categories. There were 1644 genes mapped to the KEGG pathways. This strain was assigned to the sequence type ST2 by the Pasteur MLST scheme, and harbored 32 antibiotic-resistant genes responsible for aminoglycosides, β-lactams, quinolones, phenicols, tetracyclines, fosfomycins, antifolates, erythromycin, and streptogramin resistance, in which blaOXA-23 and blaOXA-66 are responsible for carbapenem resistance. The virulome of A. baumannii VD610 consists of 36 virulence genes which are crucial for its pathogenicity. Our findings provide the genetic features of Vietnamese XDR A. baumannii sequence type ST2, which can be a reference for further study.